Gel-Based and Gel-Free Phosphoproteomics to Measure and Characterize Mitochondrial Phosphoproteins - Thongboonkerd V. (2023)
The mitochondrion is a key intracellular organelle regulating metabolic processes, oxidative stress, energy production, calcium homeostasis, and cell survival. Protein phosphorylation plays an important role in regulating mitochondrial functions and cellular signaling pathways. Dysregulation of protein phosphorylation status can cause protein malfunction and abnormal signal transduction, leading to organ dysfunction and disease. Investigating the mitochondrial phosphoproteins is therefore crucial to better understand the molecular and pathogenic mechanisms of many metabolic disorders. Conventional analyses of phosphoproteins, for instance, via western blotting, can be done only for proteins for which specific antibodies to their phosphorylated forms are available. Moreover, such an approach is not suitable for large-scale study of phosphoproteins. Currently, proteomics represents an important tool for large-scale analysis of proteins and their post-translational modifications, including phosphorylation. Here, we provide step-by-step protocols for the proteomics analysis of mitochondrial phosphoproteins (the phosphoproteome), using renal tubular cells as an example. These protocols include methods to effectively isolate mitochondria and to validate the efficacy of mitochondrial enrichment as well as its purity. We also provide detailed protocols for performing both gel-based and gel-free phosphoproteome analyses. The gel-based analysis involves two-dimensional gel electrophoresis and phosphoprotein-specific staining, followed by protein identification via mass spectrometry, whereas the gel-free approach is based on in-solution mass spectrometric identification of specific phosphorylation sites and residues. In all, these approaches allow large-scale analyses of mitochondrial phosphoproteins that can be applied to other cells and tissues of interest. © 2022 Wiley Periodicals LLC. Basic Protocol 1: Mitochondrial isolation/purification from renal tubular cells. Support Protocol: Validation of enrichment efficacy and purity of mitochondrial isolation. Basic Protocol 2: Gel-based phosphoproteome analysis. Basic Protocol 3: Gel-free phosphoproteome analysis.